Design Of Compact Pre-Pregger Machine For In House Production Of Pre-Preg Material - A Rahman, Muhamad Arfauz; Mohamad, Nor Rizan; Mustafa, Zaleha; Ismail, Syahriza; Abdul Rahman, Azrul Azwan; Abdullah, Shariman; Mohamad, Effendi; Nordin, Mohd Hisham; Salleh, Mohd Rizal (Penerbit Universiti, UTeM, 2018)
The main idea of this project is to conceptually design and simulate a lab-scale pre-pregger machine for in house production of pre-preg material. The aim is to decrease the size of the existing machine and reduce the cost to fabricate it. The concept design of the machine focuses on four major components: drum, resin bath, guider and fiber spindle. The pre-pregger machine is designed with an adaptable drum parameter which can be installed and removed easily from the drum holder. In this project, Programmable Logic Controller (PLC) was used to control the pre-pregger machine. The CXONE OMRON PLC was chosen to design the ladder diagram of the controller. In order to simulate and test the correctness of the controller, a simple electrical setup has been made. The setup consists of three motors, few sensors and push button. The simulated setup proved that the proposed conceptual design of the pre-pregger machine is workable.